Perubahan Struktur dan Pergeseran Makna Frasa Nomina Bahasa Inggris dalam “The Adventure Of Tom Sawyer” dan Versi Bahasa Indonesianya - Ruminda Ruminda; SITI KOMARIAH (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2018)
Translation is not only translating SL into TL, but also looking for the equivalent meaning when SL is translated into TL. English and Indonesian are two languages where both of them have different grammatical pattern in arranging how word, phrase, and clause as units of syntax are formed into a good sentence. This research shows how the structure and the changing meaning of NP in English and Indonesian found in The Adventures of Tom Sawyer’s novel and its Indonesian translation. The method of research is using qualitative method, purposive sampling, and document analysis which uses tri diagram. Using the theory of translation shift and syntax, this research shows that there are the changing of syntactic pattern, the changing of syntactic category and the changing of syntactic function also the shift of meaning when English NP is translated into Indonesian.